The value of work to the Elits of prophets and its influence on cultural construction (Journal of the College of Education for Women, 2019)
Praise be to Allah and peace and blessings be upon our Prophet Muhammad and on his family and companionsYet,The prophets (peace be upon them) urged all thevalues and one of these is the value of work which is of a great importance, that all nations have gathered against us as the eaters gather at a bowl. One of the reasons of our weakness and the strength of our enemy is that we have neglected the value of work. And rather a large number of ignorant and uneducatedpeople started to believe that the means of living, triumph, gaining power, and establishing a civilization are given by Allah with neithergainingnoreffort from us. While we find in the past that Allah the Almighty narrated to us the story of Mary (Peace be upon her) and how her newborn baby calls her from her below to shake the trunk of a palm tree to drop upon her ripe, fresh dates, and He is the one who created a baby to her without a father; still He did not exempt her from the efforts of work and gaining, and other examples are abundant.From this point, the meanings and denotations that are mentioned in the Holy book of Allahare ought to becomprehended - especially at this time –so that the Muslim nation rise again. And among these meanings are the values that Allah spread in the glory Quran especially the value of work.Noting that the glorious past of Muslim nation is full of instancesof the renaissance and superiority in the practical fields in comparison to the rest of nations. And today as we have all the means - from human resources to minerals and treasures that are in our land as well as creative brains - of raising and competing with other nations; yet, we still at the last position of the convoy compared to other nations.Let’s take a look at Japan for instance, they do not have a cup of oil and their land was completely destroyed in the World War II, yet, today they lead the world scientifically and technologically. So.., what is wrong with us?Finally, this is an effort of a negligent. I pray Allah the Almighty to make these words in my scale of good deeds not misdeeds.God's blessings and peace upon our Prophet Muhammad and upon his family and companions.